Was will die MFA? Eine Befragung zu der Arbeitszufriedenheit und den Wünschen von medizinischen Fachangestellten im ambulanten Bereich - Scheerbaum, Petra; Scheerbaum, Martin; Schöffski, Oliver (Gesundheitsökonomie und Qualitätsmanagement, 2024)
Aim Every sixth female entrant to a job-training in Germany pursues employment as a medical assistant. However, there is still insufficient data on the wishes of this group so far. Therefore, we want to investigate this subject. Method Using a regional digital survey, medical assistants in outpatient practices in Middle Franconia and Upper Franconia were asked about the wishes and preferences in their everyday work life. Results Overall, medical assistants are very satisfied related to their workplace as well as to the work with patients. Less approval was given to the areas of communication in the team, leadership behaviour as well as further training opportunities. Conclusion Employers should focus on an open and transparent form of discussion with their medical assistants concerning questions of decisions and personal development.
CRIS-Team Scopus Importer:2024-03-08
Keywords: healthcare professionals; job satisfaction; medical assistant; outpatient sector